Sodium-glucose cotransporter 2 inhibitors and neurological disorders: a scoping review - Thahesh Tharmaraja; Jamie S.Y. Ho; Ching-Hui Sia; Nicole-Ann Lim; Yao Feng Chong; Amanda Y.L. Lim; Rahul R. Rathakrishnan; Leonard L.L. Yeo; Vijay K. Sharma; Benjamin Y.Q. Tan (SAGE Publishing, 2022)
Background: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) are a group of antidiabetic medications with a favourable cardiovascular, renal and overall safety profile. Given the limited treatment options available for neurological disorders, it is important to determine whether the pleiotropic effects of SGLT2i can be utilised in their prevention and management. Methods: All articles published before 20 March 2021 were systematically searched in MEDLINE, EMBASE, Scopus, Web of Science, APA PsycINFO and ClinicalTrials.gov. Overall, 1395 titles were screened, ultimately resulting in 160 articles being included in the qualitative analysis. Screening and data extraction were conducted by two independent authors and studies were excluded if they were not an original research study. Findings: Of the 160 studies, 134 addressed stroke, 19 cognitive impairment, 4 epilepsy and 4 movement disorders, encompassing a range from systematic reviews and randomised controlled trials to bioinformatic and animal studies. Most animal studies demonstrated significant improvements in behavioural and neurological deficits, which were reflected in beneficial changes in neurovascular units, synaptogenesis, neurotransmitter levels and target receptors' docking energies. The evidence from the minority clinical literature was conflicting and many studies did not reach statistical significance. Interpretation: SGLT2i may exert neurological benefits through three mechanisms: reduction in cardiovascular risk factors, augmentation of ketogenesis and anti-inflammatory pathways. Most clinical studies were observational, meaning that a causal relationship could not be established, while randomised controlled trials were heterogeneous and powered to detect cardiovascular or renal outcomes. We suggest that a longitudinal study should be conducted and specifically powered to detect neurological outcomes.